Book reviews: Errornomics – Why mainstream economics will always be a dangerously ideological pseudo-science & what can be done about it with some suggestions for a better, more scientific model - Lazar, Isadora (Annals of Spiru Haret University. Economic Series, 2011)
David Wells asserts the moral right to be identified as the author of Errornomics and this pamphlet based on it. Errornomics is a pre-book (by an analogy with academic pre-papers) of 214 pp. It is described on the cover as an author’s sketch because it is a record of work-in-progress. The most important arguments are laid out in detail; the less important are just sketched. It is based on the books, Power and Economics: the Failure of Ideology, [Wells 2001]; The End of Civilisation: Science, Ideology and Irrationality, [Wells 2003], both published by Rain Press, but develops their concepts much further and in new directions.